Molecular Interaction Study of N1-p-fluorobenzyl-cymserine with TNF-α, p38 Kinase and JNK Kinase - Batool, Sidra; Sulaman Nawaz, Muhammad; H. Greig, Nigel; Rehan, Mohd; A. Kamal, Mohammad (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2013)
Alzheimer's disease (AD) is an age-related neurodegenerative disease distinguished by progressive memory loss and cognitive decline. It is accompanied by classical neuropathological changes, including cerebral deposits of amyloid- beta peptide (Aβ)containing senile plaques, neurofibrillary tangles (NFTs) of phosphorylated tau (p-tau), and clusters of activated glial cells. Postmortem studies strongly support a critical role for neuroinflammation in the pathogenesis of AD, with activated microglia and reactive astrocytes surrounding senile plaques and NFTs. These are accompanied by an elevated expression of inflammatory mediators that further drives Aβand p-tau generation. Although epidemiological and experimental studies suggested that long-term use of non-steroidal anti-inflammatory drugs (NSAIDs) may lessen AD risk by mitigating inflammatory responses, primary NSAID treatment trials of AD have not proved successful. Elevated systemic butyrylcholinesterase (BuChE) levels have been considered a marker of low-grade systemic inflammation, and BuChE levels are reported elevated in AD brain. Recent research indicates that selective brain inhibition of BuChE elevates acetylcholine (ACh) and augments cognition in rodents free of the characteristic undesirable actions of acetylcholinesterase- inhibitors (AChE-Is). Hence, centrally active BuChE-selective-inhibitors, cymserine analogs, have been developed to test the hypothesis that BuChE-Is would be efficacious and better tolerated than AChE-Is in AD. The focus of the current study was to undertake an in-silico evaluation of an agent to assess its potential to halt the self-propagating interaction between inflammation,Aβand p-tau generation. Molecular docking studies were performed between the novel BuChE-I, N1-p-fluorobenzyl-cymserine (FBC) and inflammatory targets to evaluate the potential of FBC as an inhibitor of p38, JNK kinases and TNF-αwith respect to putative binding free energy and IC50 values. Our in-silico studies support the ability of FBC to bind these targets in a manner supportive of anti-inflammatory action that is subject to molecular dynamics and physiochemical studies for auxiliary confirmation.
Keywords: Docking